Answer:
[tex]s^2Y(s)+38Y(s)=g(s)[/tex]
Step-by-step explanation:
Given the second order differential equation with initial condition.
[tex]y''+36y=g(t); \ y(0)=0, \ y'(0)=0, \ and \ y''(0)=1[/tex]
Take the Laplace transform of each side of the equation.
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
[tex]\boxed{\left\begin{array}{ccc}\text{\underline{Laplace Transforms of DE's:}}\\\\L\{y''\}=s^2Y(s)-sy(0)-y'(0)\\\\\ L\{y'\}=sY(s)-y(0) \\\\ L\{y\}=Y(s)\end{array}\right}[/tex]
Taking the Laplace transform of the DE.
[tex]y''+36y=g(t); \ y(0)=0, \ y'(0)=0, \ and \ y''(0)=1\\\\\Longrightarrow L\{y''\}+38L\{y\}=L\{g(t)\}\\\\\Longrightarrow s^2Y(s)-s(0)-0+38Y(s)=g(s)\\\\\Longrightarrow \boxed{\boxed{s^2Y(s)+38Y(s)=g(s)}}[/tex]
Thus, the Laplace transform has been applied.